Viabilitas dan jumlah produk mikoriza Kelompok Tani Ngudi Makmur di Desa Kataan Kecamatan Ngadirejo Temanggung - Ahmad Arfi Setiadi; Susiana Purwantisari (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Mycorrhiza is microbes that provide positive benefits for plants. The purpose of this study was to determine the cell number and viability of mycorrhizae product of Ngudi Makmur Temanggung Farmer Group. The study was conducted from April to May 2018. The parameters of this study were viability and number of mycorrhiza cells in vitro at PDA medium. The method used inthis research is a direct calculation method for Petri dish containing media PDA then incubated for 0,4,8 and 12 days later. The calculation of mycorrhiza using the method indirectly grown on PDA media then calculated with the formula MPN. The microbial viability was calculated by comparing the number of microbes on the x-day incubation with the initial amount of incubation. The results showed that the highest number of colonies on mycorrhiza on the first day of 94 colonies / g and the number decreased constantly with increasing days so that at the last observation the number was 63 colonies / g. The viability of mycorrhiza tended to decrease with increasing incubation time. The viability of mycorrhiza tends to decrease with increasingincubation time.